Energy use efficiency and greenhouse gas emissions (GHG) analysis of garlic cultivation in Turkey - Baran, Mehmet Firat; Demir, Cihan; Eliçin, Ahmet Konuralp; Gökdoğan, Osman (International Journal of Agricultural and Biological Engineering, 2023)
This study has been conducted with the purpose of determining energy use efficiency and greenhouse gas emissions of garlic cultivation during the 2020-2021 cultivation season in Adıyaman province of Turkey. Questionnaires, observations and field works were performed in 134 garlic farms in the region through simple random method. In garlic cultivation, energy input was calculated as 32103.20 MJ/hm2 and energy output was calculated as 30096 MJ/hm2. With regards to the three highest inputs in garlic production, 46.66% of the energy inputs consisted of chemical fertilizers energy (14979.26 MJ/hm2), 11.29% consisted of farmyard manure energy (3625.71 MJ/hm2) and 10.48% consisted of human labour energy (3363.36 MJ/hm2). Energy use efficiency, specific energy, energy productivity and net energy in garlic cultivation were calculated as 0.94, 1.71 MJ/kg, 0.59 kg/MJ, and −2007.20 MJ/hm2, respectively. The total energy input consumed in garlic cultivation was classified as 27.19% direct energy, 72.81% indirect energy, 35.17% renewable energy and 64.87% non-renewable energy. Total GHG emissions and GHG ratio were calculated as 8636.60 kgCO2-eq/hm2 and 0.46 kgCO2-eq/kg, respectively. Keywords: energy use efficiency, garlic, greenhouse gas emissions, specific energy, Turkey DOI: 10.25165/j.ijabe.20231604.7599 Citation: Baran M F, Demir C, Eliçin A K, Gökdoğan O. Energy use efficiency and greenhouse gas emissions (GHG) analysis of garlic cultivation in Turkey. Int J Agric & Biol Eng, 2023; 16(4): 63-67.